Motivasi Kerja terhadap Tingkat Kesejahteraan Pengrajin Gula Aren Kecamatan Motoling - Sembung, Sharon S.; Manoppo, Wilfried S.; Mangindaan, Joanne V. (Productivity, 2020)
This research aims to find out the effect of work motivation on the welfare level of brown sugar craftsmen in motoling sub-district. Motivational variables in the test using 5 indicators and welfare variables using 4 indicators. This research method of logic uses a quantitative research approach. The sampling technique used is probability sampling with a population of 55 respondents. The data sought from this study is the level of well-being of craftsmen and the questionnaire data shared with the Craftsmen of Brown Sugar. The results of this study show that there is a significant influence because the calculated t value of 7,761 greater than the table t value of 1,303 can be inferred ho hypothesis rejected and accepted ha hypothesis. Based on the data obtained concluded that the influence of work motivation on the welfare level of craftsmen is at a strong correlation rate of 60.2%, while 38.8% is influenced by other factors not studied in this study.